Charter and Ordinances of the City of La Crosse, with the Rules of the Common Council, at 177, Ordinance no. 14, § 19 (1888) - (:unkn) unknown (My University, 1888)
It shall be unlawful for any person to use firearms or to shoot off a gun or pistol or to hunt game or birds within the limits of any cemetery in the city of La Crosse; or to rob or disturb birds' nests therein, or to enter any cemetery except by the gate, and then only at such times as the same may be open to the public; or to enter the same as a thoroughfare in going from one place to another. Any person violating any provisions of this section, shall upon conviction, be fined in a sum not more than ten dollars, and in case of a second conviction shall be imprisoned not more than sixty days nor less than ten days.
Keywords: DISCHARGE; HUNTING REGULATION